Enhancing Charge Separation in Photocatalysts with Internal Polar Electric Fields. Issue 5 (22nd February 2017) - Lou, Zaizhu; Wang, Peng; Huang, Baibiao; Dai, Ying; Qin, Xiaoyan; Zhang, Xiaoyang; Wang, Zeyan; Liu, Yuanyuan
Abstract: The main limitations on photocatalytic efficiency are the recombination of photogenerated electrons and holes and a narrow light response. In this Minireview, we focused on photocatalytic materials with an internal polar electric field. The development and application of these compounds is one of the most efficient strategies to promote the separation of photogenerated electrons and holes, leading to high photocatalytic efficiency. This Minireview describes the fundamental operating principles of photocatalysts with a built‐in polar electric field and discusses the mechanism for polar‐electric‐field‐enhanced charge separation. We also review recent reports on photocatalytic systems using an internal polar electric field to separate photogenerated electrons and holes, focusing particularly on layer‐structure polar photocatalysts, silver silicates, and single‐crystal ZnO photocatalysts. Charge separation enhanced by an internal polar electric field provides the basis for designing new high efficiency photocatalysts. Abstract : Think inside the box : In semiconductor photocatalysis, bulk recombination of photoinduced electron–hole pairs severely limits photocatalytic efficiency. This Minireview focuses on the recent development of materials with an internal polar electric field which have been found to be highly efficient in photocatalytic reactions, and discusses the mechanism of polar‐electric‐field enhanced charge separation.